ISOLATION DAN CHARACTERIZATION OF AN ORGANIC SOLVENT STABLE LIPASE FROM PSEUDOMONAS STUTZERI ISOLATED FROM MUD CRATER ÃâÃâBLEDUG KUWUÃâÃâ PURWODADI CENTRAL JAVA - PUTU PARWATA (NIM : 20510029); Pembimbing : Dr. Rukman Hertadi, I
Lipase (triacylglycerol hydrolase, EC 3.1.1.3) is an enzyme that catalyze the hydrolysis of water-insoluble long-chain triglicerides. Nowadays lipase has also been applied to catalyze the synthesis of organic compounds. Therefore, it is demanded to have lipase that stable in organic solvents. Lipase that is stable under extreme conditions, such as in high concentration of organic compound, are generally isolated from microorganisms living in extreme environments (extremophiles). One of them is halophilic microorganisms that can live in environments with high salinity or low water activitythat is similar to the environment with high level of organic compounds. Therefore, it can be expected that extracellular lipases released from this type of microorganism will also stable in organic solvents. In this study, we cultivated microorganism isolated from salty water emerge from the mud crater of "Bleduk Kuwu" located in Kuwu Vilage of Grobongan Regency in Central Java. The aim of this work is thus to obtained potential microorganism that can produce organic solvent-stable lipase. In order to obtain potential microorganism, the salty water from the mud crater were grown at 37oC for 48 hours in liquid Luria Bertani medium (LB) composed of 0.1% tryptone, 0.05% yeast extract, and 5% NaCl. A total of 20 well-grown colonies were randomly selected and tested for the tolerance to NaCl levels using medium composed of 0.1% tryptone, 0.05% yeast extract, 2% bacto agar, and 0-30% NaCl. All colonies were then examined for lipolytic potency using medium with a composition of 0.5% peptone, 0.5% yeast extract, 0.05% CaCl2, 5% NaCl, and 2% bacto agar, substrate suspension (2.5% olive oil, 1.0% tween 80), and 2.0% Rhodamin B. Colonies that showed lipolytic activity was isolated from the mixtures using four quadrants spread and strike techniques. A single isolated bacteria was identified using some techniques, i.e. GramÃ‚Â’s staining, analysis of 16s rRNA gene and construction of phylogenetic tree. Lipase was produced from a single isolate using liquid medium composed of 0.5% peptone, 0.5% yeast extract, 0.05% CaCl2, and 0.1% NaCl. Lipase crude extract fractionated using acetone and ammonium sulfate in three range of concentrations, i.e. 0-40%, 40-60% and 60-80%. The molecular weight of lipase was estimated by SDS-PAGE and zymogram. The concentration of protein was determined by Bradford technique using bovin serum albumine (BSA) as the standard. Lipase was characterized biochemically in order to obtain optimum pH and temperature, to study effect of metal ions, detergents and inhibitors, as well as to examine the effects of organic solvents. Lipase activity was measured using the substrate of pnitrophenyl palmitate (pNPP) by measuring the absorbance of p-nitrophenol (pNP) released from the catalytic process at a wavelength of 405 nm. Lipase activity is expressed in units/mg, i.e. μmol of pNP (products) produced by the lipase per minute per mg of enzyme. The results showed that most of the colonies acquired to grow well in medium with salt concentrations from 5 to 27.5%, but there are only three colonies able to survive in salt levels up to 7.5%. The result of lipolytic potency test showed one colony produce lipase, which has tolerancy to NaCl levels from 0 to 7.5% (belong to moderate halophilic). The morphology of the single isolated colony has bacillus shape and it was belong to a group of gram-negatif bacteria. The phylogenetic analysis showed the bacteria belong to Pseudomonas stutzeri. The best results of lipase fractionation provides at a fraction of 40-60% with specific activity of 10.5 units/mg and 12.8 units/mg for fractionation with acetone and ammonium sulphate, respectively. The results of SDS-PAGE and zymogram showed that the obtained lipase has a molecular weight of 29 kDa. Lipase showed optimum activity at pH 8.5 and temperature 50oC. Lipase was stable after incubation for one hour at a temperature of 40Ã‚Â°C, and able to maintain its activity up to 74% after incubation for one hour at a temperature of 50oC. Lipase activity increased with the presence of ions such as Zn2+ and Ba2+, but decreased by ions such as Cu2+ and Fe2+. Inhibitor PMSF did not significantly inhibit the activity of lipase suggesting that the enzyme probably is not included in serine hydrolases group. Lipase is able to maintain its activity up to 56% after incubation for 1 hour in 50 mM Glicin-NaOH buffer (pH 8.5) containing 10 mM EDTA, which indicates the lipase does not belong to metalloenzymes group. The obtained lipase was also stable against some polar organic solvents such as methanol, ethanol, and acetone, as well as non-polar organic solvent such as n-hexane. Therefore, the obtained lipase is potential to be applied as a biocatalyst in organic synthesis reactions. This study thus has successfully to obtain an organic solvent-stable lipase from halophilic bacteria isolated from the mud crater of "Bledug KuwuÃ‚Â”